Increasing Awareness of the Village Disaster Risk Reduction Forum in Magetan Regency in Realizing Disaster Preparedness - Sunarto Sunarto; Heru Santoso Wahito Nugroho; Suparji Suparji (Health Dynamics, 2024)
Disaster risk reduction forums as a capacity in disaster resilient villages often experience difficulties in realizing disaster preparedness. It is necessary to prioritize any element that is immediately realized, so that what is done truly makes society have resilience and toughness. five disaster preparedness parameters that must be prepared by the forum. These five parameters have 25 elements as constructs. Elements as a construct of disaster preparedness parameters become an instrument called Difficulty and Usefulness of Elements in Disaster Preparedness (DUEDP-Questionnaire). This DUEDP questionnaire serves as a guide enumerator for interviewing forum administrators and communities in 23 disaster-resilient villages in the Magetan district. Data was collected for three months starting May-July 2023. The element prioritization technique uses the Quadrant of Difficulty and Usefulness (QoDU) method. This method focuses on elements in the upper left quadrant, namely elements that are very useful but how to make it happen is very difficult. The research results place the elements of involving vulnerable groups in socializing about disasters, providing village funds for disaster management, preparing contingency plan documents, providing early warning system tools, and training families to provide disaster preparedness bags as the main priorities that must be immediately realized by the forum.